Predicting Criminal Recidivism Using "Split Population" Survival Time Models - Ann Dryden Witte
In this paper we develop a survival time model in which the probability of eventual failure is less than one, and in which both the probability of eventual failure and the timing of failure depend (separately) on individual characteristics. We apply this model to data on the tiring of return to prison for a sample of prison releasees, and we use it to make predictions of whether or not individuals return to prison. Our predictions are more accurate than previous predictions of criminal recidivism. The model we develop has potential applications in economics: far example, it could tie used to model the probability of default and the timing of default on loans.